2019
DOI: 10.1371/journal.pone.0212085
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the load-velocity profile in the free-weight prone bench pull exercise through different velocity variables and regression models

Abstract: This aims of this study were (I) to determine the velocity variable and regression model which best fit the load-velocity relationship during the free-weight prone bench pull exercise, (II) to compare the reliability of the velocity attained at each percentage of the one-repetition maximum (1RM) between different velocity variables and regression models, and (III) to compare the within- and between-subject variability of the velocity attained at each %1RM. Eighteen men (14 rowers and four weightlifters) perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 27 publications
8
47
0
4
Order By: Relevance
“…However, the lower correlations between the BP variants observed in this study for V 1RM compared to V last suggest that the V 1RM could also be less reliable than V last . This would corroborate the results of previous studies that have reported a poor reliability for the V 1RM during the BP (Pestaña-Melero et al, 2018) and other resistance training exercises such as the back squat (Banyard, Nosaka & Haff, 2017), deadlift (Ruf, Chery & Taylor, 2018), or bench pull (García-Ramos et al, 2019b). Another limitation is that the BP was performed in a Smith machine, while the vast majority of athletes use the free-weight BP during their resistance training programs.…”
Section: Exercisesupporting
confidence: 85%
See 1 more Smart Citation
“…However, the lower correlations between the BP variants observed in this study for V 1RM compared to V last suggest that the V 1RM could also be less reliable than V last . This would corroborate the results of previous studies that have reported a poor reliability for the V 1RM during the BP (Pestaña-Melero et al, 2018) and other resistance training exercises such as the back squat (Banyard, Nosaka & Haff, 2017), deadlift (Ruf, Chery & Taylor, 2018), or bench pull (García-Ramos et al, 2019b). Another limitation is that the BP was performed in a Smith machine, while the vast majority of athletes use the free-weight BP during their resistance training programs.…”
Section: Exercisesupporting
confidence: 85%
“…Previous studies have selected the minimal velocity threshold as either the individualized V 1RM (Banyard, Nosaka & Haff, 2017;Ruf, Chery & Taylor, 2018) or a general V 1RM for all subjects (García-Ramos et al, 2018a, 2019a. The assessment of the individualized V 1RM is associated with at least two problems: (I) the individual is required to perform a lift against the 1RM load and (II) the individual V 1RM has been demonstrated to be an unreliable metric for a number of exercises such as the back squat (coefficient of variation (CV) = 22.5%, intraclass correlation coefficient (ICC) = 0.42) (Banyard, Nosaka & Haff, 2017), deadlift (CV = 15.7%, ICC = 0.63) (Ruf, Chery & Taylor, 2018), Smith machine bench press (BP) (CV = 13.9-15.7%, ICC = 0.54-0.64) (Pestaña-Melero et al, 2018), or bench pull (CV = 6.36%, ICC = 0.18) (García-Ramos et al, 2019b). Therefore, it would be of interest to investigate whether the minimal velocity threshold (i.e., velocity value used to estimate the 1RM from the individualized L-V relationship) can be obtained with a higher reliability using other approaches that do not require the individual to perform a lift against the 1RM load.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of differences between the BP variants for the magnitudes of V 1RM and V last simplifies this approach because the same minimal velocity threshold could be used for both BP variants. According to the results of this and previous studies, the minimal velocity threshold should be set at 0.17 m•s -1 (García-Ramos et al, 2018;García-Ramos et al, 2019;González-Badillo & Sánchez-Medina, 2010;Sánchez-Medina, González-Badillo, Pérez, & Pallarés, 2014). However, Helms et al (2017) reported in 15 powerlifters (12 men and 3 women) a lower V 1RM during the free-weight BP exercise that was performed using a "press" command to simulate a powerlifting competition.…”
Section: Discussionmentioning
confidence: 93%
“…Movement velocity has been proposed as an accurate variable for estimating the 1repetition maximum (1RM) during a number of resistance training exercises (García-Ramos & Jaric, 2018;McBurnie et al, 2019). Early studies proposed generalized loadvelocity (L-V) relationship equations to estimate the percentage of 1RM from the velocity value recorded against a submaximal load lifted with maximal effort (González-Badillo & Sánchez-Medina, 2010). The basic premise of generalized L-V relationship equations is that a given velocity represents the same percentage of 1RM for all individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation